Two Evaniosomini species (Coleoptera: Tenebrionidae) associated with decaying carcasses in Argentina, with remarks on the tribal assignment of Achanius Erichson: Coleopterists Bulletin - Flores, Gustavo Ernesto (2015)
Thinobatis profana Kulzer is transferred from Thinobatis (Pimeliinae: Thinobatini) to Vaniosus Kulzer (Pimeliinae: Evaniosomini) on the basis of constant tribal level characters. The genus Thinobatis Eschscholtz is thereby removed from the Argentine fauna and confined only to coastal areas of Chile. The genus Achanius Erichson (including the subgenus Ambigatus Fairmaire) is transferred from Edrotini (Eurymetopini of Doyen) to Evaniosomini based on the structure of the internal female reproductive tract and mandible configuration. Achanius (Ambigatus) antofagastensis Flores and Aballay, new species, is described. Redescriptions of Thinobatis, Vaniosus, and Achanius, with habitus photographs, SEM images, and illustrations of female genital features, are provided. The eating habits of V. profana and A. antofagastensis feeding on decomposing pig and llama carcasses are given for the first time. These two species showed preferences for microhabitat conditions and association with stages of decomposition. They should be considered for potential forensic importance on bodies found in arid environments.